USM, UMB ESTABLISHES COLLABORATIVE NETWORK IN COMMUNICATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 9 September 2016 – A collaborative network has been established with the signing of a Memorandum of Agreement (MoA) in the field of Communication between Universiti Sains Malaysia (USM) and Universitas Mercu Buana (UMB), Yogyakarta, Indonesia in a brief ceremony here held recently.